Strategi Pengelolaan Ekowisata Di Taman Wisata Alam Danau Tes Kabupaten Lebong - Aptawan, Hendrivan; Cahyadinata, Indra; Johan, Yar; Yurike; Brata, Bieng; Saputra, Rizki (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
This study aims to analyze the management strategy of the ecotourism area in the Tes Lake Nature Tourism Park in an integrated and sustainable manner. This study was conducted from August to December 2021 at the Tes Lake Nature Tourism Park, Lebong Regency, Bengkulu Province. The study was conducted using a non-experimental method, namely descriptive exploratory. Community perceptions and participation in the management of the ecotourism area in the Tes Lake Nature Tourism Park were analyzed descriptively. Furthermore, the analysis of the management strategy for the Tes Lake Nature Tourism Park ecotourism area was carried out using a SWOT analysis. The results of the study showed that most respondents had good perceptions and participation in the natural ecosystem of Tes Lake, Lebong Regency. The position of the Tes Lake ecotourism management strategy is in quadrant I, namely the position with an aggressive strategy (S-O). In this case, the recommended strategy is to utilize the strengths of the Tes Lake ecotourism, namely beautiful natural scenery, cool and beautiful air, support from the Regional Government and the Balai Management, the friendliness of the surrounding community and the richness of local wisdom and customs. Keywords: Participation, Perception, Strategy, Tes Lake Ecotourism